Polyvinyl chloride-added dibutyl adipate for high-performance electrohydrodynamic pumps - Shimizu, Keita; Murakami, Kazuya; Ogawa, Naoki; Akai, Hideko; Shintake, Jun (Frontiers in Robotics and AI, 2023)
Electrohydrodynamic (EHD) pumps are a promising driving source for various fluid-driven systems owing to features such as simple structure and silent operation. The performance of EHD pumps depends on the properties of the working fluid, such as conductivity, viscosity, and permittivity. This implies that the tuning of these parameters in a working fluid can enhance the EHD performance. This study reports a method to modify the properties of a liquid for EHD pumps by mixing an additive. Specifically, dibutyl adipate (DBA) and polyvinyl chloride (PVC) are employed as the working fluid and the additive, respectively. The results show that when the concentration of PVC is 0.2%, the flow rate and pressure at applied voltage of 8 kV take highest value of 7.85 µL/s and 1.63 kPa, respectively. These values correspond to an improvement of 109% and 40% for the flow rate and pressure, respectively, compared to the pure DBA (PVC 0%). When the voltage is 10 kV, the flow rate of 10.95 µL/s and the pressure of 2.07 kPa are observed for DBA with PVC concentration of 0.2%. These values are more than 5 times higher than those observed for FC40 at the same voltage (2.02 µL/s and 0.32 kPa). The results also suggest that optimal conductivity and viscosity values exist for maximizing the EHD performance of a liquid. This demonstrates the validity of the proposed method for realizing high-performance EHD pumps by using additives in the working fluid.